1973
DOI: 10.2134/agronj1973.00021962006500020004x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids and Palatability of Phalaris arundinacea L. Grown in Diverse Environments1

Abstract: We grew 15 clones of reed canarygrass (Phalaris arundinacea L.) of varying palatability in Indiana and Minnesota and nine clones in Pennsylvania and Alaska over a 2‐year period to determine whether diverse environments would influence alkaloid type, alkaloid concentration, and palatability. We also determined the repeatability of a previously‐established correlation between palatability and total basic alkaloids in reed canary. Major alkaloid types and relative total basic alkaloid concentrations of clones wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Simons and Martin (1971) and Martin et al (1973) have shown a good correlation between palatability in this species, as determined by using sheep, and total alkaloids. Their methods of alkaloid analyses involved either the independent anaiysis of indoles or a total alkaloid analysis.…”
Section: Paiatability Of Reedmentioning
confidence: 69%
“…Simons and Martin (1971) and Martin et al (1973) have shown a good correlation between palatability in this species, as determined by using sheep, and total alkaloids. Their methods of alkaloid analyses involved either the independent anaiysis of indoles or a total alkaloid analysis.…”
Section: Paiatability Of Reedmentioning
confidence: 69%
“…Germination requires light and is best in moist soils (Vose, 1962;Landgraff and Junttila, 1979;Zedler, 2001, 2002b), with highest germination rates in water-saturated soils (Coops and Vandervelde, 1995;Kellogg et al, 2003). RCG has a naturally high concentration and diversity of alkaloids from the tryptamine, carboline, gramine, and hordenine families (Marten et al, 1973;Coulman et al, 1977;Ostrem, 1987), which make the species naturally poorly palatable (Marten et al, 1973(Marten et al, , 1976Thompson et al, 2001).…”
Section: A General Features Of Reed Canary Grass In Itsmentioning
confidence: 99%
“…Moreover it acts as an efficient water purifier in the same way as other Helophytes like Scirpus lacustrk (Le R o n and Lepine, 1985), Phragmites austrah (Pautou, 1975;Dubois, 1977), and Cladium mariscus (Pautou, 1981). Its high productivity (7 to 12 tons of dry matter ha-' yr-' in the case of the aboveground part according to Marten, 1985), has made it a widely used forage plant (Berg, 1980;Foss, 1983) at least at the very first stages'of its growth because toxicity increases with maturation (Marten et al, 1973;Gomm, 1979).…”
Section: Introductionmentioning
confidence: 99%